Ecorestoration of the coalmine degraded lands - Maiti, Subodh Kumar; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2013)
The book adopts an application-oriented approach for ecorestoration of coalmine degraded. The theoretical aspects of ecorestoration, and steps involved in ecorestoration process and experimental aspects of thorough analytical procedures have been discussed in detail. It emphasizes on the types of mining, land degradation, and biodiversity conservation while giving details of technical and biological steps, topsoil management, selection of plant species, seeding, nursery practices; adoption of innovative approaches like mulching, biofertlizer application, hydroseeding, superabsorbent; use of grass-legume mix; monitoring and aftercare of reclaimed sites; the indicators of sustainable ecorestoration; and Rules and Acts implemented and followed across the world. Rest of the text to be uploaded with the manuscript as this box has limitiations.
SECTION A.-Chapter 1: INTRODUCTION.-Chapter -2: Ecology and Ecosystem in Mine Dedraded Land.-CHAPTER 3: PHYSICAL (TECHNICAL) RECLAMATION.-Chapter 4: Minesoil properties affecting plant establishment and growth.-Chapter 5: Topsoil Management.-Chapter 6: Programs and Planning of vegetation cover development.-Chapter 7: Seeds – collection, storage & treatment.-Chapter 8: NURSERY RAISING OF SAPLINGS FOR FOREST TREES -- Chapter 9: Establishment of Grasses and Legumes Cover.-Chapter 10 Application of Mulch, geotextiles and amendments.-Chapter 11: Bio-fertilizer (Mycorrhiza) technology in Mine Ecorestoration.-Chapter -12: Biodiversity, Erosion and Conservation in Ecorestored site.-Chapter 13: Monitoring and Aftercare of Ecorestored Site.-Chapter 14: Evaluation of Reclamation success and Soil Quality Indicators.-Chapter – 15: Forest & Wildlife Conservation Acts.-Chapter 16: Ecological Impact Assessment of Surface Mining Project.-Chapter 17: MINE CLOSURE.- SECTION B.-Chapter 1 : SAMPLING TECNIQUE.-Chapter 2 : ANALYSIS OF PHYSICAL PARAMETERS.-Chapter 3: ANALYSIS OF CHEMICAL PARAMETERS OF SOIL AND OVERBURDEN.-Chapter 4: SOIL MICROBIOLOGICAL PARAMETERS.-CHAPTER 5: PLANT ANALYSIS, FIELD TRIALS AND VEGETATION SURVEY.-Annex: SOIL ANALYSIS.-Annex- 1: Soil Analysis -- Annex- 2:   Apparatus/ Instruments required for sol analysis laboratory.                   .
Keywords: Environmental sciences; Landscape ecology; Fossil fuels; Nature conservation; Environmental Science and Engineering; Landscape Ecology; Fossil Fuels (incl. Carbon Capture).; Nature Conservation